2016
DOI: 10.1111/jne.12407
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Name? Roles of RFamide‐Related Peptides Beyond Gonadotrophin Inhibition

Abstract: RFamide-related peptides (RFRPs) have been heavily implicated in the control of reproductive function subsequent to their discovery more than 16 years ago. However, recent studies using genetic and pharmacological tools have challenged their importance in regulating the hypothalamic-pituitary-gonadal axis. It is generally accepted that RFRPs act as part of a wider RFamide system, which involves two receptors, called the neuropeptide FF receptors (NPFFR1 and R2), and includes the closely-related neuropeptide NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…For example, Hcrt not only promotes arousal, but also regulates feeding, energy homeostasis, reward seeking and addiction ( Li et al, 2016 ). Previous studies of RFRP peptides in birds and rodents have demonstrated roles in regulating reproductive behaviors and nociception ( Kim, 2016 ; Kriegsfeld et al, 2015 ; Tsutsui et al, 2010 ; Tsutsui et al, 2012 ; Tsutsui et al, 2015 ; Ubuka et al, 2014 ), and a study in zebrafish implicated NPVF neurons in nociception ( Madelaine et al, 2017 ), but a role in sleep has not been reported. The rodent and avian studies mostly used infusion of single, in vitro synthesized RFRP peptides that, in addition to potentially lacking post-translational modifications that may be necessary for normal function, do not take into consideration the combinatorial action of RFRP peptides to promote sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hcrt not only promotes arousal, but also regulates feeding, energy homeostasis, reward seeking and addiction ( Li et al, 2016 ). Previous studies of RFRP peptides in birds and rodents have demonstrated roles in regulating reproductive behaviors and nociception ( Kim, 2016 ; Kriegsfeld et al, 2015 ; Tsutsui et al, 2010 ; Tsutsui et al, 2012 ; Tsutsui et al, 2015 ; Ubuka et al, 2014 ), and a study in zebrafish implicated NPVF neurons in nociception ( Madelaine et al, 2017 ), but a role in sleep has not been reported. The rodent and avian studies mostly used infusion of single, in vitro synthesized RFRP peptides that, in addition to potentially lacking post-translational modifications that may be necessary for normal function, do not take into consideration the combinatorial action of RFRP peptides to promote sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The human NPVF preproprotein produces three mature peptides, known as RFamide-related peptide (RFRP) 1, RFRP2, and RFRP3 ( Hinuma et al, 2000 ). In rodents, intracerebroventricular infusion of synthetic RFRP1 or RFRP3 has been reported to affect hormone levels, food intake, sexual behavior and nociception ( Kim, 2016 ; Kriegsfeld et al, 2015 ; Liu et al, 2001 ; Tsutsui et al, 2015 ; Ubuka et al, 2012 ). RFRP1 and RFRP3 can bind to NPFFR1 and NPFFR2 in mammalian cell culture, but RFRP2 does not and its cognate receptor(s) remains unknown ( Hinuma et al, 2000 ; Liu et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…NPFF utilizes two receptors, NPFFR1 and NPFFR2, which also represent new therapeutic targets [ 168 ]. NPFF and different RFRPs do have similar effects: they do share the NPFFR1; however, further effects in mammals are not well researched yet [ 169 ]. A connection with the HPA and HPG axis in relation to NPFF receptors has been studied.…”
Section: Neuropeptides In Anxiety and Depressionmentioning
confidence: 99%
“…FLP-13 peptides are characterized by an amidated Arginine-Phenylalanine (RFamide) motif at their C-termini. RFamide neuropeptides are involved in many physiological functions in both invertebrates (López-Vera et al, 2008; Peymen et al, 2014), and vertebrates (Rőszer and Bánfalvi, 2012; Kim, 2016). In fruit flies, several RFamide neuropeptides regulate sleep (He et al, 2013; Shang et al, 2013), including the RFamide neuropeptide FMRFamide, which regulates SIS (Lenz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%